Effectiveness of adjunctive Xiao-er Kechuanling to terbutaline and montelukast in children with uncontrolled asthma: a prospective observational cohort study - Luo, Shutao; Li, Cuiyuan; Huo, Shaojin (Frontiers in Pediatrics, 2025)
BackgroundAchieving optimal control in childhood asthma remains challenging, particularly with therapies like short-acting beta2-agonists (SABA) plus leukotriene receptor antagonists (LTRA). Xiao-er Kechuanling (XKL), a traditional Chinese medicine formula with demonstrated anti-inflammatory and bronchodilatory effects, presents a potential adjunctive therapy. This study aimed to compare the clinical effectiveness and safety of adjunctive XKL added to terbutaline (SABA) and montelukast (LTRA) (Triple Therapy) vs. terbutaline plus montelukast alone (Dual Therapy) in children with uncontrolled asthma.MethodsThis single-center, prospective observational cohort study enrolled children aged 6–14 years with uncontrolled asthma (ACT ≤ 19) receiving either Dual or Triple Therapy based on physician prescription, with no inhaled corticosteroid use for ≥3 months prior. Participants were followed for 6 months. Primary outcomes included the proportion achieving ≥3-point ACT score increase, severe exacerbation frequency, and changes in serum (TGF-β1, MMP-9/TIMP-1 ratio) and HRCT (WT/D ratio) remodeling markers. Secondary outcomes included lung function (FEV1/FVC, PEF variability), inflammatory markers (IL-4, IL-13, ECP), and safety.Results199 children were enrolled (95 Dual, 104 Triple); 94 Dual and 88 Triple completed the 6-month follow-up. Baseline characteristics were comparable between groups (P > 0.05). At Month 6, a significantly higher proportion in the Triple Therapy cohort achieved ≥3-point ACT increase (85.2% vs. 61.7%, P = 0.002). Triple Therapy was associated with significantly greater reductions in serum TGF-β1 (P = 0.017), MMP-9/TIMP-1 ratio (P < 0.001), and HRCT WT/D ratio (P = 0.017). Significantly greater improvements in FEV1/FVC (P = 0.002) and PEF variability (P < 0.001), and greater reductions in IL-4 (P = 0.015), IL-13 (P = 0.032), and ECP (P = 0.011) were also observed in the Triple Therapy group at Month 6. Exacerbation frequency was numerically lower but not significantly different (P = 0.125). Safety profiles, including adverse event rates, were comparable (P > 0.05).ConclusionIn this observational study, adding XKL to terbutaline and montelukast was associated with significant improvements in asthma control, lung function, and markers of inflammation and airway remodeling in children with uncontrolled asthma over 6 months, with a comparable safety profile. However, due to the observational design and lack of confounder adjustment, these findings indicate association, not causality. Randomized controlled trials are needed to confirm the effectiveness of this adjunctive therapy.